The Mapping of Sustainability Index in Small and Medium Enterprises: A Case Study in Lampung Indonesia - Lintang Harwina Madyaratry; Hartrisari Hardjomidjojo; Elisa Anggraeni (Jurnal Teknik Industri, 2020)
Small-medium enterprises (SMEs) generally have constraints on their performance efficiency and productivity. It affects the ability of SMEs to compete in the global market. Therefore, the mapping of SME conditions needs to be analyzed. This study aims to map the SME conditions and find out SME’s sustainability index. This study uses a multidimensional scaling method through ecological, social, economic, technological, and institutional dimensions. A case study was carried out at Banana Chips SMEs in Lampung Province. These SMEs are the mainstays of Lampung Province. The results show that the SME condition was divided into three categories: poor, good, and very good. The status of the sustainability of SMEs in each dimension was divided into two groups: the poor category for the technology dimension and the good category both for the ecological, social, economic, and institutional dimensions. The results of the mapping of SME’s sustainability index produced several improvement strategies for SMEs.